Drilling studies on Particle Board composite using HSS twist drill and spade drill. (2018) - Kumar, A. Madhan; Jayakumar, K.
Abstract: Composite materials are finding increased application in different engineering fields due to its favorable properties. In composites, wood based composites are natural composites in which particle board (PB) is extensively used in domestic and commercial purposes mainly in wood based furniture. Among different machining processes, drilling is the most generally used machining process in wood working industry for assembly operations. But during drilling, delamination at entry and exit sides of a hole, edge chipping, surface damage, etc are the major damages occur during drilling of PB composites. Therefore, study of effect of drilling parameters and cutting environment on machining of PB composite is an important area and it needs a detailed analysis. In this study, drilling of PB composite using HSS twist drill and spade drill of ∅ 10 mm is investigated. The objectives of the study are to measure and analyze the effect of process parameters on surface roughness and drilling time of PB for the two different drills. Process parameters considered are spindle speed (rpm), feed (mm/rev) and machining environment (Dry, Flood coolant and Kerosene). Drilling experiments were performed on 10 mm thickness board based on L9 orthogonal array using twit drill and spade drill with the total of 18 experiments and average surface roughness (Ra) of all drilled holes surface was measured. From the results obtained with twist drill, machining time is decreased from 11.81 to 2.03 seconds with an increase of speed (S) and feed (f) for kerosene. Similarly, machining time is decreased from 18.54 to 2.97 sec with increase of "S" and "f" for the same kerosene with spade drill. With increase of "S" and "f" using kerosene, the Ra is decreased from 15.593 to 9.711 µm for twist drill. In the same way, the Ra is decreased from 15.3 to 10.083 µm with increase of "S" and "f" using kerosene for spade drill.